2020
DOI: 10.1159/000506121
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the 3-Year Persistence Rate with Second-Line Vedolizumab and Tumor Necrosis Factor-α Inhibitors in Patients with Inflammatory Bowel Disease Followed in Gastroenterology Practices in Germany

Abstract: Background: Our goal was to investigate the 3-year persistence rates with second-line vedolizumab and tumor necrosis factor-α (TNF-α) inhibitors (i.e., adalimumab, golimumab, infliximab) in patients with inflammatory bowel disease (IBD) who were followed in gastroenterology practices in Germany. Methods: This study included patients aged ≥18 years who had received prescriptions for second-line biological drugs in Germany between 2014 and 2017 (n = 5,150) retrieved from the longitudinal prescription database. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
0
3
1
Order By: Relevance
“…Two recent German studies reported that vedolizumab was associated with better treatment persistence, both as first and second line agent, compared with anti-TNFα agents. 105 , 106 Such findings are in contrast with the results of the VICTORY consortium, where anti-TNF agents were reported to have better persistence compared with vedolizumab in CD patients. 107 Considering that IBD are life-long conditions that usually arise in young adults, 108 further investigations on the best strategies to maintain long-term remission are needed.…”
Section: Combination and Sequential Therapies For A Dynamic Management Of Ibdcontrasting
confidence: 69%
“…Two recent German studies reported that vedolizumab was associated with better treatment persistence, both as first and second line agent, compared with anti-TNFα agents. 105 , 106 Such findings are in contrast with the results of the VICTORY consortium, where anti-TNF agents were reported to have better persistence compared with vedolizumab in CD patients. 107 Considering that IBD are life-long conditions that usually arise in young adults, 108 further investigations on the best strategies to maintain long-term remission are needed.…”
Section: Combination and Sequential Therapies For A Dynamic Management Of Ibdcontrasting
confidence: 69%
“…Helwig et al [78] evaluated more than 5000 patients who had received prescriptions for second-line biologic drugs in Germany between 2014 and 2017. Vedolizumab users were matched to adalimumab, golimumab, and infliximab users based on age, sex, and index year.…”
Section: Comparison Between Anti-tnf and Vedolizumab Treatment In Anti-tnf Experienced Patientsmentioning
confidence: 99%
“… 27–29 The results of Chen et al’s study 27 were used as a source of persistence data for infliximab and adalimumab in the first line of treatment. Helwig et al’s studies 28 , 29 were used as a data source for vedolizumab in the first line of treatment and all biologic treatments in the subsequent lines. Because persistence at year 1 in the base case was based on the 1-year maintenance data from clinical studies, long-term persistence rate was recalculated using real-world studies with 1 year as the starting point.…”
Section: Methodsmentioning
confidence: 99%